A reterritorialização e o direito originário como reconquista da terra e dos territórios dos povos indígenas do Médio rio Solimões (AM) - Ivani Ferreira de Faria; Carla Cetina Castro; Diego Ken Osoegawa (Confins)
This article analyses how the indigenous peoples of the Médio rio Solimões recover their lands and territories through the processes of reterritorialization and ethnogenesis, which constitute a strategy of resistance for the maintenance of life as a people, as culture. Through participative methodologies, such as workshops of knowledge management and participative mapping, 47 indigenous lands were identified, some of them which are demarcated (25) while others have not been measured (22). The proposition of common use and possession of the same territory by different peoples of a single land who have been violently deterritorialized demonstrates the recovery of their territories by reversing the situation and creating new territorialities in the face of the phenomenon of ethnogenesis or resistance to the process of colonial assimilation, in order to avoid future conflicts of use and enable the process of recognition of their lands by competent institutions.